Non‐linear coefficient of BaTiO3‐doped ZnO varistor. Issue 6 (1st November 2013) - Kharchouche, Fayçal; Belkhiat, Saâd; Belkhiat, Djamel Eddine Chouaib
Abstract : The effect of additions up to 9.6%wt BaTiO3 on grain growth and microstructure in ZnO samples sintered at 1300°C has been studied using scanning electron microscopy, energy dispersive X‐ray, X‐ray diffraction and impedance analyser as techniques. The sample doped with 1.6%wt BaTiO3, leads to grain size increasing and forms (BaO10.89 Ti3.93 Zn2.03 and Ba4 O27 Ti11 Zn) solid solutions with ZnO. A homogeneous structure was obtained whereas with further additions 3%wt the structure was inhomogeneous and the solid solutions formed in the first segregate to grain boundaries. Afterwards, an excess of 9.6%wt BaTiO3 leads to BaTiO3 phase segregation locating on the surface of the sample and in the grain boundaries near the junctions between matrix grains. Experimental I–V current‐voltage characteristics show that BaTiO3 as additive in ZnO varistors, increases the non‐linear coefficient (α) and the breakdown voltage. The highest non‐linearity was obtained for 9.6%wt BaTiO3 content with α = 121.03 and 1.79 µA in leakage current. The average breakdown voltage per grain boundary (Vgb) was evaluated in the ranges 1.7–3.46 V/gb and 1.34–2.54 V/gb in agreement with the literature.